The comprehensive interactomes of human adenosine RNA methyltransferases and demethylases reveal distinct functional and regulatory features - Covelo-Molares, Helena; Obrdlik, Ales; Poštulková, Ivana; Dohnálková, Michaela; Gregorová, Pavlína; Ganji, Ranjani; Potěšil, David; Gawriyski, Lisa; Varjosalo, Markku; Vaňáčová, Štěpánka (Nucleic acids research, 2021)
N6-methyladenosine (m6A) and N6,2'-O-dimethyladenosine (m6Am) are two abundant modifications found in mRNAs and ncRNAs that can regulate multiple aspects of RNA biology. They function mainly by regulating interactions with specific RNA-binding proteins. Both modifications are linked to development, disease and stress response. To date, three methyltransferases and two demethylases have been identified that modify adenosines in mammalian mRNAs. Here, we present a comprehensive analysis of the interactomes of these enzymes. PCIF1 protein network comprises mostly factors involved in nascent RNA synthesis by RNA polymerase II, whereas ALKBH5 is closely linked with most aspects of pre-mRNA processing and mRNA export to the cytoplasm. METTL16 resides in subcellular compartments co-inhabited by several other RNA modifiers and processing factors. FTO interactome positions this demethylase at a crossroad between RNA transcription, RNA processing and DNA replication and repair. Altogether, these enzymes share limited spatial interactomes, pointing to specific molecular mechanisms of their regulation.
Keywords: Protein Binding; N-demethylasy; adenosin; gen pro FTO; Adaptor Proteins, Signal Transducing; Protein Isoforms; RNA, Messenger; RNA, Untranslated; methyltransferasy; AlkB Homolog 5, RNA Demethylase; HEK293 buňky; anotace sekvence; Transcription, Genetic; mapování interakce mezi proteiny; HEK293 Cells; jaderné proteiny; protein - isoformy; nekódující RNA; Protein Interaction Mapping; genetická transkripce; DNA Repair; oprava DNA; vazba proteinů; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; lidé; Oxidoreductases, N-Demethylating; Humans; Methyltransferases; adaptorové proteiny signální transdukční; Molecular Sequence Annotation; replikace DNA; DNA Replication; genová ontologie; Adenosine; Gene Ontology; Nuclear Proteins; messenger RNA; alfa-ketoglutarát-dependentní dioxygenasa, AlkB homolog 5